Women in the Social Policy of the Second Polish Republic - Pawel Grata (European Scientific Journal, ESJ, 2017)
The system of support for women within the framework of the social policy of the Second Polish Republic included: the adequate regulations of work legislation, the rules of social insurance, the activities towards the maternity protection of the insured and, finally, social services directly or indirectly provided to women by the central as well as local governments. These activities were extensive and, in many cases, very modern. What is more, they were directed towards solving the most important social problems of women. However, rather than common, the scope of those activities was very limited and selective. Moreover, the implementation of those activities was not always in accordance with the plans and expectations of their authors. From the point of view of the existing social needs, the most advanced solutions were those which resulted from a privileged position of women in the work legislation and the system of health insurance. The problem of the insignificant influence always had its roots in the socio-professional structure of the country. Only women in employment or covered by the insurance could receive the benefits. For the rest the offer was no longer that beneficial.